The Transformation of Topêng Dhâlâng Top Dance Movements in The Sumenep Style Puspawarna Dance Form - Rahayu, Eko Wahyuni; Sudrajat, Arief; Handaningrum, Warih; Sasanadjati, Jajuk Dwi (Fakultas Ilmu Sosial dan Politik, Universitas Negeri Surabaya, 2024)
Sumenep style Puspawarna Dance, is one of the relatively new forms of choreography based on Madurese ethnic dance, which was created in 2021 by a team of lecturers from Surabaya State University (UNESA). The Sumenep style Puspawarna Dance, in the form of a women's group dance, supported by five dancers, has the theme of offerings, which depicts the girls performing offerings as an expression of gratitude, a request for welfare, and salvation (reject reinforcements). This article aims to reveal about the construction of the Sumenep style Puspawarna Dance form as a result of the transformation of dance movement patterns in Madura topêng dhâlâng performances. The process of movement transformation in the Sumenep Style Puspawarna Dance is carried out through the adoption of several basic movement patterns of male dance in topêng dhâlâng, then adapted or changed to suit the concept of dance forms and themes through distortion and stylization techniques. The results of movement transformation in Puspawarna Dance can enrich the diversity of patterns and movement techniques of Madurese style princess dance, especially Sumenep style. In addition, the results of the transformation of the Sumenep style Puspawarna Dance movement can strengthen the characteristics of the Madurese ethnic princess dance style.